THE INFLUENCE OF SUPPORT AND INFORMATION SYSTEM TOWARD THE USE OF WORK INFORMATION IN BUDGETING WITH DEVELOPMENT FACTOR AS INTERVENING VARIABLE - Pepie Diptyana; Hardo Basuki (Journal of Economics, Business, and Accountancy Ventura, 2010)
This research is dealt with political factors using internal and external organization supports as proxy. Besides that, it also uses information system as variables that influence work performance measurement development as well as the utilization of performance information in budgeting. This research attempts to test and confirm whether such factors are consistently influential toward work performance measurement development and utilization of performance information in budgeting as conducted by the previous studies. It uses random sampling system,consisting of 316 executives with the echelon ranks of 2, 3, and 4 at the regional government offices, Jogjakarta, Indonesia. This research reveals that political factor influence utilization of performance information in budgeting, both directly and indirectly through performance measurement development. In addition, information system capability, incapabilityof explaining and assessing performance metrics (as technical factors) do not influence either directly or indirectly both work performance measurement development and utilization of performance information in budgeting. Yet, another technical factor, which is technical knowledge, has significant influence toward work performance measurement development in budgeting. These findings imply that the change into performance measurement-based budgeting is influenced by the regional government’s internal and external support, external participations such as society for escorting the regional government officials in facing the budgeting system change.